Autumn passage of soaring birds over Dobrogea (Romania): a migration corridor in Southeast Europe - Fülöp, Attila; Pârâu, Liviu G. (Ardea, 2018)
The Dobrogea region in southeastern Romania, which is part of the Eurasian-East African Flyway, is listed as one of the important migration corridors for soaring birds on the western coast of the Black Sea. However, our knowledge regarding migration intensity, phenology and geographical patterns of soaring birds over the area is poor. To determine the migration intensity and phenology of soaring birds, we recorded the autumn migration in the Măcin Mountains (northern Dobrogea) from mid-August to the end of October between 2002-2007. To describe the geographical patterns of migration at a regional scale, we recorded migration intensity in the second half of September in 2010 and 2011, simultaneously from 15 and 13 counting points, respectively, covering the entire region of Dobrogea. In the Măcin Mountains we recorded a mean number (±SD) of 11,297 ± 2333.5 (CV = 20.7%) migrating raptors per year, and of 21,367 ± 10,949.3 (51.2%) and 455.6 ± 43.6 (9.6%) migrating White Storks Ciconia ciconia and Black Storks Ciconia nigra, respectively. Migration phenology parameters varied across raptor and non-raptor species. Migration occurred over a broad front, covering all of Dobrogea. However, migration intensity was more pronounced in the western, central and eastern parts of the region, and was less intensive in the northern central areas. Overall, we recorded 30 migrating raptor species and three non-raptor species. The most abundant raptors were Common Buzzard Buteo buteo, European Honey Buzzard Pernis apivorus, Lesser Spotted Eagle Clanga pomarina, Eurasian Sparrowhawk Accipiter nisus and Western Marsh Harrier Circus aeruginosus. The three non-raptor species were White Stork, Black Stork and Great White Pelican Pelecanus onocrotalus. Our study provides the first general overview of the autumn passage of soaring birds over Dobrogea, highlighting the importance of this area as part of a global migration network.
Gesehen am 09.08.2019